Facilitating collaborative animal research: The development and implementation of a Master Reciprocal Institutional Agreement for Animal Care and Use. Issue 2 (26th April 2020) - Holthaus, Kathryn; Goldberg, David; Connelly, Carolyn; Corning, Brian; Nascimento, Christina; Witte, Elizabeth; Bierer, Barbara E.
Abstract: Ensuring appropriate review, approval, and oversight of research involving animals becomes increasingly complex when researchers collaborate across multiple sites. In these situations, it is important that the division of responsibilities is clear and that all involved parties share a common understanding. The National Institutes of Health Office of Laboratory Animal Welfare and the United States Department of Agriculture Animal Plant Health Inspection Service require an Institutional Animal Care and Use Committee (IACUC) to review the care and use of animals in research, and both agree that it is acceptable for one IACUC to review the work taking place at multiple institutions. With this in mind, several Harvard-affiliated hospitals and academic centers developed the Master Reciprocal Institutional Agreement for Animal Care and Use (Master IACUC Agreement) to support collaboration, decrease administrative burden, increase efficiencies, reduce duplicative efforts, and ensure appropriate protections for animals used in research. Locally, the Master IACUC Agreement has fostered greater collaboration and exchange while ensuring appropriate review and oversight of research involving animals. As multisite animal protocols become more prevalent, this Agreement could provide a model for a distributed, national network of IACUC reliance.